Análise experimental do desempenho termo-hidráulico de nanofluidos de nanotubos de carbono em escoamento monofásico - Hoffmann, Antonio Remi Kieling (2014)
The present research deals with an experimental study of the heat transfer and pressure drop of nanofluids composed by carbon nanotubes and distilled water in single-phase flow inside a horizontal straight tube. An experimental bench has been developed and constructed whose the main component was a horizontal brass tube electrically heated by tape resistors wrapped on the external surface. Experimental results have been obtained for a wide range of mass velocities, 600 up to 3200 kg/s.m2, (Reynolds varying from 2300 to 30000) corresponding to the transition and turbulent flow regimes. The specific heat flux varied from 10 to 18 kW/m2. Tests were conducted for three different temperatures at the test section inlet, 10, 15 and 20 C. Other effects on the heat transfer coefficient were also analyzed such as: aspect ratio of the carbon nanotubes; mass concentration and nanoparticle deposition on the wall. The thermal-hydraulic performance obtained for the nanofluid was higher in comparison with distilled water.The experimental results were compared with the leading correlations from the literature. Finally, an empirical correlation for the heat transfer coefficient was proposed, with a very good agreement in relation to the experimental results using nanofluids.